2013
DOI: 10.1007/s11325-013-0829-0
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the 5-hydroxytryptamine 2A/2C receptor genes and 5-hydroxytryptamine transporter gene in Chinese patients with OSAHS

Abstract: The A1438G polymorphism of the 5-HTR 2A gene might be involved in the pathogenesis in OSAHS subjects of the Chinese Han population. Meanwhile, our findings support the argument that 5-HTT polymorphism appears to be associated with susceptibility to OSAHS, because the allele 10 of 5-HTT-VNTR might be a susceptible factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Another area of research used in sleep disorder breathing is the study of serotonin transporter gene (5-HTT) polymorphism, responsible for the interactions between serotonin and its receptors, in order to control the reuptake of serotonin and the peripheral actions of 5-HT. 38 The encoding 5-HTT gene is located in the 17q11.1-17q12 region of Chromosome 17, as shown in Figure 1. 74 Previous studies have identified two polymorphisms of this gene (5-HTTLPR and 5-HTTVNTR), also illustrated in Figure 1, that influence the intrasynaptic serotonin concentration and are implicated in sleep disorder, psychological diseases, and other associated OSA phenotypes, as seen in Table 1.…”
Section: Serotonin Transporter Genementioning
confidence: 99%
See 1 more Smart Citation
“…Another area of research used in sleep disorder breathing is the study of serotonin transporter gene (5-HTT) polymorphism, responsible for the interactions between serotonin and its receptors, in order to control the reuptake of serotonin and the peripheral actions of 5-HT. 38 The encoding 5-HTT gene is located in the 17q11.1-17q12 region of Chromosome 17, as shown in Figure 1. 74 Previous studies have identified two polymorphisms of this gene (5-HTTLPR and 5-HTTVNTR), also illustrated in Figure 1, that influence the intrasynaptic serotonin concentration and are implicated in sleep disorder, psychological diseases, and other associated OSA phenotypes, as seen in Table 1.…”
Section: Serotonin Transporter Genementioning
confidence: 99%
“…This evidence suggests that there is a positive association between OSA and 5-HTT polymorphism and that the allele 10 of 5-HTTVNTR might become a susceptible factor in the development of sleep disorders. 38 Kunugi et al conducted a study that took into account the serotonin transporter gene polymorphism in patients with bipolar affective disorders and found that there are significant ethnic differences between the Chinese Han and European American population in terms of genotype or allele frequencies of 5-HTTLPR and STin2.VNTR in the 5-HTT gene. 75 Similar to the study of Yue et al, which stipulated that the allele 10 repeat of STin2.VNTR was associated with OSA in both total and male subjects and that the L allele showed significant differences between OSA male and male controls, the study of Chen et al revealed same results.…”
Section: Dovepressmentioning
confidence: 99%
“…In summary, for outcomes >1 available study, a meta-analysis was performed for polymorphisms such as angiotensin-converting enzyme insertion/deletion (ACE I/D)[ 28 – 35 ], tumor necrosis factor (TNF)-α-308G/A[ 27 , 36 – 39 ], interleukin (IL)-6[ 40 , 41 ], 5-hydroxytryptamine receptor (5-HTR) 2A-102T/C[ 42 – 44 ] and -1438G/A[ 42 – 45 ], 5-HTR2C-796 C/G[ 42 , 44 ], 5-hydroxytryptamine transporter gene-linked promoter region (5-HTTLPR)[ 36 , 45 – 47 ], 5-HTT variable number tandem repeat (5-HTTVNTR)[ 44 47 ], leptin receptor (LEPR) Gln223Arg[ 48 – 50 ], peroxisome proliferator-activated receptor (PPAR-γ) Pro12Ala[ 51 , 52 ], apolipoprotein E (APOE) ε2/ε4[ 53 , 54 ], β1-adrenergic receptor (ADRB1)[ 55 , 56 ] and ADRB2[ 55 , 57 ]. Candidate genes identified from included studies were summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Certain studies have been conducted to investigate the association of OSAHS with the polymorphisms of the 5-HTR2A genes with the 'T' and 'C' allele. Bayazit et al (17) reported on Turkish patients with OSAS, de Carvalho et al (18) reported on Brazilian patients with OSAS, Sakai et al (19) reported on Japanese patients with OSA, and Chen et al (20) and Yin et al (21), reported on Chinese patients with OSAS. All these studies showed that genotypes and allele frequencies of the T102C (rs6311) polymorphism of 5-HTR2A did not significantly increase the OSAS risk.…”
Section: Male N (%) Female N (%) ----------------------------------mentioning
confidence: 99%